Fabrication of tunable 3D graphene mesh network with enhanced electrical and thermal properties for high-rate aluminum-ion battery application. Issue 53 (16th May 2016) - Yang, G. Y.; Chen, L.; Jiang, P.; Guo, Z. Y.; Wang, W.; Liu, Z. P.
Abstract : Three-dimensional (3D) graphene networks are attracting ever-increasing attention in the field of energy storage because their unique architecture at macroscopic scales is beneficial for effective electron and ion transport. Abstract : Three-dimensional (3D) graphene networks are attracting ever-increasing attention in the field of energy storage because their unique architecture at macroscopic scales is beneficial for effective electron and ion transport. Herein, a novel interconnected 3D graphene mesh network (3D GMN) was successfully designed and fabricated by folded Ni meshes assisted chemical vapor deposition method. The structure parameters of 3D GMN can be controlled well by tuning the period of Ni mesh and the electroplating time. With the increase of the density of 3D GMN, the electrical conductivity of 3D GMN and the thermal conductivity of 3D GMN/epoxy composite are greatly improved compared to that of the 3D graphene foam. This 3D GMN enables the high capacity of 57 mA h g −1 in an aluminum ion battery at the ultra-high rate of 40C with capacity retention of 96.5% after 200 cycles.